Comparison of healthcare costs of patients with COPD on maintenance inhaled therapies between 2011 and 2019 in Hungary using a nationwide database - Brigitta Dombai; Viktória Nagy; István Ruzsics; László Németh; Tamás Balázs; Balázs Sánta; Zsófia Lázár (PLoS ONE, 2025)
Introduction and objectives Medical costs of patients with chronic obstructive pulmonary disease (COPD) are high, however data from Eastern European countries are scarce. We aimed to study healthcare payments for patients with COPD on maintenance inhaled therapy in Hungary and analyse the trends and influencing factors between 2011 and 2019 in a retrospective financial database analysis. Patients We collected data of patients from the Hungarian National Insurance Fund, who were > 40 years old, received maintenance inhaled therapy > 90 days within 12 months prescribed for J41-44 International Classification of Diseases-10 codes. All-cause and COPD-specific healthcare costs were compared between 2011 and 2019. We used a generalized mixed regression model to analyse the effects of calendar years, age, sex, Charlson comorbidity index, status of incidence, annual duration of inhaled therapy, the number of COPD-related hospitalization and geographical regions. Results We analysed the data of 227 254 patients. In 2019, cumulative all-cause and COPD-specific spendings reached 401.15 million and 118.14 million USD, respectively. Annual total and COPD-related costs per patient in 2011 vs. 2019 were 2707 ± 3598 vs. 3332 ± 4463 USD and 927 ± 1162 vs. 981 ± 1534 USD, respectively (mean ± standard deviation). The increase in all-cause costs was above, while the rise in COPD-related costs was below the Hungarian inflation rate. The costs of medication and inpatient care comprised of the highest payment segments. The number of COPD-related hospitalizations had the most significant effect on the expenditures, while comorbidity burden and spendings on inhaled maintenance therapy were related to all-cause and COPD-specific costs, respectively. Increasing age was associated to higher spendings, but women had lower costs. Conclusions The costs of inpatient care and medication are responsible for the largest segments of healthcare spendings for patients with COPD. Prevention of hospitalizations due to COPD and the close follow-up of comorbidities can help reduce medical costs.